Digital subtraction cisternography: a new approach to fistula localisation in cerebrospinal fluid rhinorrhoea. Issue 12 (December 1990) - Byrne, J V; Ingram, C E; MacVicar, D; Sullivan, F M; Uttley, D
Abstract : Positive contrast cisternography with digital subtraction of fluoroscopy images before computed tomography (CT) was employed in the investigation of eight patients with cerebrospinal fluid (CSF) rhinorrhoea. Fistulae were visualised by preliminary digital subtraction cisternography (DSC) in six patients and in five patients the sites of leakage were confirmed at surgery. Fluoroscopy facilitated interpretation of CT in all the positive studies and in two patients provided information which could not be deduced from CT cisternography (CTC) alone. The combined technique is recommended for the investigation of patients with recurrent and post operative CSF rhinorrhoea and when CTC alone fails to identify the site of leakage.